ANALISIS JARINGAN DOKTOR PENDIDIKAN AGAMA ISLAM DI UIN SUNAN AMPEL SURABAYA SEBAGAI INVISIBLE COLLEGE - Amira Oribia Wanda Sasmita; Bayu Indra Pratama; Joko Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the network of doctoral students in Islamic Religious Education at UIN Sunan Ampel Surabaya as an invisible college through promotional activities. Relational data on 79 collections of doctoral dissertations in the repository from 2012 to 2024 and 14 dissertations in hardcopy form in the Library under 2012 were analyzed using Social Network Analysis (SNA) with NodeXL and UCINET software. Cultural data from all dissertations were also used to understand the characteristics of invisible colleges in the form of study specializations. The results show that invisible colleges are formed through promotional activities with sub-groups that share common institutions, methods, and studies, where popular and strategic actors are promoters or co-promoters at UIN Sunan Ampel Surabaya. The actors play an important role in the network, while the isolated actors have the longest range. The findings also show indications of academic inbreeding. Invisible colleges are formed through promotional activities with key actors playing an important role in networking, as well as suggesting the use of new software and approaches for more in-depth analysis, expanding studies to other doctoral or comparative inter-institutional programs, and improving scientific documentation and archiving to support more comprehensive meta-analysis research.